1994
DOI: 10.1002/jmv.1890430412
|View full text |Cite
|
Sign up to set email alerts
|

Different antibody response to a neutralizing epitope of human cytomegalovirus glycoprotein B among seropositive individuals

Abstract: The amino-terminal portion of human cytomegalovirus glycoprotein B (HCMV-gB) was expressed as a fusion protein to analyze the neutralizing epitope recognized by human monoclonal antibody C23 and the humoral immune response to this epitope. The linear neutralizing epitope was further localized to the peptide within 17 amino acids (position 68-84) which were conserved between two HCMV laboratory strains. Ten out of 17 HCMV-seropositive human sera contained the antibody against this epitope. Although seven sera w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The other antigenic site maps between amino acids 68 and 84; it is highly conserved among HCMV strains and is recognized by human mAbs with complement-independent neutralizing activity. However, it was recently reported that approximately half of the human sera tested reacted with a fusion protein constructed to express these amino acid sequences [Ayata et al, 1994]. Results of the present study support the idea that the strain-common epitopes located in the extreme amino-terminal sequence of gB elicit antibodies in some, but not all, HCMV-infected individuals.…”
Section: Discussionsupporting
confidence: 88%
“…The other antigenic site maps between amino acids 68 and 84; it is highly conserved among HCMV strains and is recognized by human mAbs with complement-independent neutralizing activity. However, it was recently reported that approximately half of the human sera tested reacted with a fusion protein constructed to express these amino acid sequences [Ayata et al, 1994]. Results of the present study support the idea that the strain-common epitopes located in the extreme amino-terminal sequence of gB elicit antibodies in some, but not all, HCMV-infected individuals.…”
Section: Discussionsupporting
confidence: 88%
“…We observed that fewer than 20% (23/140) of the individuals that we sampled in our cohort of healthy subjects had detectable serum levels of antiM2e antibodies. The reasons for this phenomenon are not clear, but a similar situation exists in human CMV, where only a minority of human CMV-seropositive subjects has measurable antibodies to the broadly conserved, neutralizing AD2 epitope within the gB complex of human CMV (25,37,38).…”
Section: Resultsmentioning
confidence: 99%
“…This antigen contains a set of neutralization epitopes, among which antigenic domains 1 (Utz et al ., 1989 ) and 2 (AD-2) (Meyer et al ., 1992 ) are the best characterized. AD-2 is, however, not very immunogenic and induces antibodies in only a fraction of infected individuals (Ayata et al ., 1994 ; Meyer et al ., 1992 ; Navarro et al ., 1997 ; Schoppel et al ., 1997 ). The effective neutralization mediated by AD-2-specific antibodies in vitro has warranted extensive studies and even clinical trials using such reagents (Azuma et al ., 1991 ), despite the fact that only very few antibodies recognizing this epitope have ever been developed (Masuho et al ., 1987 ; Ohlin et al ., 1993 ).…”
Section: Full Textmentioning
confidence: 99%